Effect of different joint angles on the mechanical strength of adhesive-bonded scarf and double butt-lap joints - Yanen, Cenk; Solmaz, Murat Yavuz (Walter de Gruyter Gmbh, 2022)
The effect of different joint angles and joint types in adhesively bonded joints was investigated. Two joint types were chosen to examine the effect of the joint type. A total of 12 samples were produced at six different angles (30 degrees, 45 degrees, 52 degrees, 60 degrees, 75 degrees, and 90 degrees) to examine the effect of joint angle on the scarf and double butt-lap joint types. St 37 steel was used as the adherend material. The adhesion distance, sample thickness, and adhesion area were kept constant in the samples. There were differences in the sample widths to make the angle change by keeping the adhesive bonding length constant. 3M Scotch-Weld DP810 epoxy adhesive was used as the adhesive. The adhesive thickness was chosen as 0.1 mm. An axial tensile load was applied to the samples, and the results were recorded and evaluated. When scarf and double butt-lap joint samples are compared with each other according to their angles, it was seen that double butt-lap joints were more successful in samples with 30, 45, and 52 degrees joint angles, and scarf lap joints were more successful in samples with 60, 75, and 90 degrees joint angles.
Keywords: adhesive; double butt-lap joints; joint angle; scarf lap joints; tension